Analisis Perbandingan Upah Minimum Provinsi (UMP) antara Pulau Jawa dan Luar Pulau Jawa Tahun 2024 Menggunakan Uji Mann-Whithney - Jannah, Miftahul; Septianingtias, Indri Avisa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to find out whether there is a significant difference of the Provincial Minimum Wage (MWP) between Java Island and Outer Java regions in 2024. The method used is the Mann-Whithney Test as one of the independent two-sample nonparametric tests. The data used were secondary data from official government websites. The analysis results showed that there was a difference in UMP between both regions with a significance level of 10%, however it was not significant at a significance level of 5%. This suggests that UMP differences between regions are not yet sufficiently statistically robust at stricter levels.